Detection of spontaneous tumorigenic transformation during culture expansion of human mesenchymal stromal cells. (January 2014) - Pan, Qiuwei; Fouraschen, Suomi MG; de Ruiter, Petra E; Dinjens, Winand NM; Kwekkeboom, Jaap; Tilanus, Hugo W; van der Laan, Luc JW
Human mesenchymal stem/stromal cells (MSCs) have been explored in a number of clinical trials as a possible method of treating various diseases. However, the effect of long-term cell expansion in vitro on physiological function and genetic stability is still poorly understood. In this study, MSC cultures derived from bone marrow and liver were evaluated for the presence of aberrant cells following long-term expansion. In 46 independent cultures, four batches of transformed MSCs (TMCs) were found, which were all beyond the culture period of five weeks. These aberrant cells were first identified based on the appearance of abnormal cytology and the acquirement of growth advantage. Despite common MSC markers being diminished or absent, TMCs remain highly susceptible to lysis by allogenic natural killer (NK) cells. When transplanted into immunodeficient mice, TMCs formed sarcoma-like tumors, whereas parental MSCs did not form tumors in mice. Using a combination of high-resolution genome-wide DNA array and short-tandem repeat profiling, we confirmed the origin of TMCs and excluded the possibility of human cell line contamination. Additional genomic duplication and deletions were observed in TMCs, which may be associated with the transformation event. Using gene and microRNA expression arrays, a number of genes were identified that were differentially expressed between TMCs and their normal parental counterparts, which may potentially serve as biomarkers to screen cultures for evidence of early transformation events. In conclusion, the spontaneous transformation of MSCs resulting in tumorigenesis is rare and occurs after relatively long-term (beyond five weeks) culture. However, as an added safety measure, cultures of MSCs can potentially be screened based on a novel gene expression signature.